Corrective Feedbacks and Their Implications on Learners’ Uptakes in Academic Speaking Class - Didik Hartono (LPPM Universitas Mercu Buana Yogyakarta, 2018)
This study attempts to investigate a study on corrective feedbacks and learners’ uptakes in adult EFL classroom. The study was aimed at finding the types of corrective feedbacks were used by the academic speaking lecturer, the types of oral feedbacks were the most effective in the lecturer’s opinion, the types of uptakes followed lecturer’s corrective feedbacks, and the types of oral corrective feedbacks were mostly preferred by the students. The study employed a qualitative research design through a passive-participatory observation of patterns of error treatment in an adult EFL class. The research subjects were the lecturer and twenty seven students of the Academic Speaking Class, the English Department of Faculty of Culture Studies, Brawijaya University, Malang. The findings show that the lecturer applied explicit correction mostly (90%), compared to another five types of corrective feedbacks. Moreover, the lecturer said that explicit correction was the most effective type of corrective feedbacks. Meanwhile, the findings also show that most student applied repetition type of uptake. On the other hand, most of the students answered that their preference of corrective feedback type was repetition corrective feedback.